Interpretasi Vulkanostratigrafi Daerah Mamuju Berdasarkan Analisis Citra Landsat-8 - Indrastomo, Frederikus Dian; Sukadana, I Gde; Saepuloh, Asep; Harsolumakso, Agus Handoyo; Kamajati, Dhatu (BRIN Publishing, 2015)
Mamuju and its surrounding area are constructed mainly by volcanic rocks. Volcanoclastic sedimentary rocks and limestones are laid above the volcanic rocks. Volcanic activities create some unique morphologies such as craters, lava domes, and pyroclastic flow paths as their volcanic products. These products are identified from their circular features characters on Landsat-8 imagery. After geometric and atmospheric corrections had been done, a visual interpretation on Landsat-8 imagery was conducted to identify structure, geomorphology, and geological condition of the area. Regional geological structures show trend to southeast – northwest direction which is affects the formation of Adang volcano. Geomorphology of the area are classified into 16 geomorphology units based on their genetic aspects, i.e Sumare fault block ridge, Mamuju cuesta ridge, Adang eruption crater, Labuhan Ranau eruption crater, Sumare eruption crater, Ampalas volcanic cone, Adang lava dome, Labuhan Ranau intrusion hill, Adang pyroclastic flow ridge, Sumare pyroclastic flow ridge, Adang volcanic remnant hills, Malunda volcanic remnant hills, Talaya volcanic remnant hills, Tapalang karst hills, Mamuju alluvium plains, and Karampuang reef terrace plains. Based on the Landsat-8 imagery interpretation result and field confirmation, the geology of Mamuju area is divided into volcanic rocks and sedimentary rocks. There are two groups of volcanic rocks; Talaya complex and Mamuju complex. The Talaya complex consists of Mambi, Malunda, and Kalukku volcanic rocks with andesitic composition, while Mamuju complex consist of Botteng, Ahu, Tapalang, Adang, Ampalas, Sumare, danLabuhanRanau volcanic rocks with andesite to leucitic basalt composition. The volcanostratigraphy of Mamuju area was constructed based on its structure, geomorphology and lithology distribution analysis. Volcanostratigraphy of Mamuju area is classified into Khuluk Talaya and Khuluk Mamuju. The Khuluk Talaya consists of Gumuk Mambi, Gumuk Malunda, and Gumuk Kalukku, while Khuluk Mamuju consists of Gumuk Botteng, Gumuk Ahu, Gumuk Tapalang, Gumuk Adang, Gumuk Ampalas, Gumuk Sumare, and Gumuk Labuhan Ranau.